On the occurrence of parasitic plant Balanophora fungosa J.R. Forster & G. Forster (Balanophoraceae) in Andhra Pradesh, India - J. Prakasa Rao (Journal of Threatened Taxa, 2015)
Balanophora fungosa J.R. Forster & G. Forster (Balanophoraceae), a holoparasitic species is recorded as an addition to the flora of Andhra Pradesh, India.  It is described here along with its distribution and threats.  Field photographs have been provided to facilitate identification of the species.